Teaching Short Prayers to Students with Cerebral Palsy Using a Multisensory Approach at MIM PK Kartasura - Mita Nur Khasanah; Retno Pangestuti (Lembaga Yasin AlSys, 2025)
Despite increasing scholarly interest in inclusive Islamic religious education, limited attention has been given to the application of multisensory instructional techniques for teaching short prayers to children with Cerebral Palsy. This study investigates the implementation of multimodal methods and their influence on engagement and prayer pronunciation skills among students with physical disabilities. Adopting a qualitative methodology with a phenomenological case study design, the research involved one student with Cerebral Palsy, a classroom teacher, a special education assistant, and the student’s parents, selected through purposive sampling. Data were collected through participant observation, semi-structured interviews, and documentation, and analyzed thematically. The findings reveal that the integration of incremental aural stimulation, visual supports, adaptive kinesthetic activities, and tactile engagement significantly improved recall, pronunciation confidence, and emotional involvement in the prayer-learning process. These outcomes highlight the pedagogical value of multisensory learning frameworks within inclusive Islamic education and underscore the importance of collaborative instructional design involving both educators and families. The study contributes to the discourse on accessibility in religious pedagogy and suggests avenues for further research across varied educational settings and learner populations.